Learning English Grammar in a meaningful context - de Manuel Rimbau-Masnou, Berta (My University, 2023)
This project seeks to put into practice the current education paradigm, the constructivist model, based on looking at the students as active agents of their own learning and to rethink the role of the teacher in the whole process. To turn these ideas into a reality, the new education law, together with some studies based in language learning, the Universal Design of Learning and Helen Doron’s Early Childhood methodology have joined forces to find a fun, engaging and meaningful way of teaching and learning English Grammar. Studying sea life is the learning situation offered to the students to foster their knowledge, self-confidence, self-responsibility and mastery of the act of communication. Thus, providing the proficiency of language in their own common benefit.
Keywords: teaching English grammar; learning situation; meaningful learning; Universal Design of Learning; Grado en Maestro en Educación Primaria